Ecological interventions to prevent and manage zoonotic pathogen spillover. (12th August 2019) - Sokolow, Susanne H.; Nova, Nicole; Pepin, Kim M.; Peel, Alison J.; Pulliam, Juliet R. C.; Manlove, Kezia; Cross, Paul C.; Becker, Daniel J.; Plowright, Raina K.; McCallum, Hamish; De Leo, Giulio A.
Abstract : Spillover of a pathogen from a wildlife reservoir into a human or livestock host requires the pathogen to overcome a hierarchical series of barriers. Interventions aimed at one or more of these barriers may be able to prevent the occurrence of spillover. Here, we demonstrate how interventions that target the ecological context in which spillover occurs (i.e. ecological interventions) can complement conventional approaches like vaccination, treatment, disinfection and chemical control. Accelerating spillover owing to environmental change requires effective, affordable, durable and scalable solutions that fully harness the complex processes involved in cross-species pathogen spillover. This article is part of the theme issue 'Dynamic and integrative approaches to understanding pathogen spillover'.